COVID-19 Outbreak: Insights about Teaching Tasks in a Chemical Engineering Laboratory - Sergio Nogales-Delgado; Silvia Román Suero; José María Encinar Martín (MDPI AG, 2020)
Apart from the evident tragedy that the COVID-19 outbreak has meant regarding both personal and economic costs, the normal functioning of the academic year has been drastically altered at all educational levels. Regarding Spain, the state of alert implemented by the government from mid-March to June has affected traditional face-to-face sessions at universities, as they were forbidden and replaced by online lessons. The aim of this work was to explain our own experience during the COVID-19 outbreak in a chemical engineering laboratory at the University of Extremadura, concerning the university teaching and the final degree project follow-up, whose method of teaching was active and participatory, based on constructivism and focused on the student as the center of the learning process. Thus, the confinement affected both the teachers and students differently, depending on the degree of completion of their main tasks and their previous skills with computing and virtual tools, among other factors. The existence of an operating virtual campus and an online library has made the transition to total e-learning and telework easier for teachers and students.